(untitled) (Journal of Adat Recht, 2024)
A traditional law (hukum adat) is a law reflecting an Indonesian character; as a result it has been claimed as the law which is genuinely Indonesian. As an unwritten law, nowadays the existence of traditional law is questionable. It has been judged as conservative, stiff, primitive old fashioned comparing to the development of modern society. Some people argue that traditional law is unable to resolve the problems in this globalization era. In facts, traditional law has become a basic principle to legalize the contemporary laws. For instances, traditional laws inspires the law of UU. No 5 Th. 1960 about the major law of agrarian affairs and the la of UU. No. 1 Th. 1974 about marriage. The relevance of traditional law to current one is supported by the existence of UU. No. 4 Th. 2004 about the authority of judicial affairs, it opens the chance for the judges to execute and decide a case based on traditional laws.